The function of the search in journals in the study of the composition of Reinações de Narizinho, by Monteiro Lobato The function of the search in journals in the study of the composition of Reinações de Narizinho, by Monteiro Lobato - BERTOLUCCI, Denise Maria de Paiva (2007)
The search in journals had an essential function in the development of the study about the composition of the book Reinações de Narizinho, by Monteiro Lobato. So, the purpose of this article is to detail some results that we have got with the access to these printed sources, that are available in the institutes of search of the public universities from the state of São Paulo.